Marketing Research / Measurement, Method and Application - Kent Raymont (International Thomson Business Press, 1999)
This book provides a comprehensive and detailed coverage of all the elements that go into marketing research including the instruments of data capture, data collection methods and data analysis, along with an up-to-date review of techniques and applications currently used by the larger market research agencies. Preface, Acknowledgements, Marketing Research in Perspective, The Nature of Data and the Measurements of Variables, The Instruments of Data Capture, Data Collection Methods, Sampling Cases, Data Analysis, Specific Techniques and Applications, Index.